Intelligent Cloud Computing: First International Conference, ICC 2014, Muscat, Oman, February 24-26, 2014, Revised Selected Papers - al Saidi, A (Springer, 2015)
This book constitutes the refereed post-conference proceedings of the First International Conference on Intelligent Cloud Computing, held in Muscat, Oman, in February 2014. The 10 revised full papers presented were carefully reviewed and selected from 18 submissions. The papers cover topics in the areas of resource management and energy efficiency and security. They include 5 invited talks from leading organizations working in cloud computing in Oman and in the region.